Assessment of Muscarinic Receptor Subtypes in Human and Rat Lower Urinary Tract by Tissue Segment Binding Assay - Abu Syed Md Anisuzzaman; Shigeru Morishima; Fumiko Suzuki; Takashi Tanaka; Hatsumi Yoshiki; Zakia Sultana Sathi; Hironobu Akino; Osamu Yokoyama; Ikunobu Muramatsu (Elsevier, 2008)
Muscarinic receptors in the human and rat lower urinary tract (urinary bladder detrusor muscle and mucosa, and prostate) were identified by intact tissue segment binding assays with two radioligands, and the effects of prolonged receptor activation in vitro on muscarinic receptors were examined. Hydrophilic [3H]-NMS and hydrophobic [3H]-QNB bound to the detrusor muscle segments with the same density, suggesting that the muscarinic receptors were localized at the plasma membrane. While the density of muscarinic receptor was higher in detrusor muscle than in the bladder mucosa and prostate, there was no species-specific difference either in density or in subtype distribution (M1, M2, and M3subtypes in detrusor; M2and M3subtypes in bladder mucosa; and M1and M2subtypes in prostate). Incubation of detrusor strips with carbachol decreased [3H]-NMS binding sites within 20 min, followed by a reduction of [3H]-QNB binding sites after a 60-min lag phase. The loss of the binding sites over 3 h after carbachol treatment was the same (approximately 40%) for both radioligands. The present intact tissue segment binding assay reveals tissue-specific and plasma membrane distribution of distinct muscarinic receptor subtypes and their dynamic changes (internalization and down-regulation) in lower urinary tract of humans and rats. Keywords:: urinary bladder (detrusor, mucosa), prostate, muscarinic receptor, tissue segment binding assay, down-regulation